Tantangan Penegakan Hukum Hak Kekayaan Intelektual dalam Pengembangan Ekonomi Kreatif di Era Revolusi Industri 4.0 - Sutra Disemadi, Hari; Kang, Cindy (Jurnal Komunikasi Hukum, 2021)
Currently, the world is facing changes in the industrial world which can be called the Industrial Revolution 4.0, and this phenomenon has a significant impact on industrial life, namely in the form of rapid technological developments. The rapid development of technology has resulted in a new term ‘creative economy’ in which creativity and human thinking are applied. Intellectual Property Rights play a very important role in the creative economy, and the state must provide legal protection for intellectual property as a form of appreciation to creators/inventors for their efforts and hard work in producing new innovations, and minimizing the occurrence of intellectual property rights violations. However, in practice, there are several challenges and difficulties in enforcing laws related to intellectual property rights in Indonesia. This scientific journals uses normative research methods, based on written regulations and literature studies that examine aspects of theory, structure, and legal explanations. The main problems that occurs in Indonesia is the lack of public= awareness and education regarding intellectual property, and this problem can be the root of other problems. The protection of intellectual property rights in Indonesia not only provides a sense of security and legal certainty for creators/inventors, but also provides a psychological impact and increases the enthusiasm of creators/inventors to continue to innovate.